Estudo comparativo in vitro da resistência ao cisalhamento de sistemas adesivos em dentina humana: uso de hipoclorito de sódio em sistemas convencionais ou primers acidificados - Pucci, Cesar Rogério [UNESP] (2002)
The aim of this study was to investigate comparatively in vitro the shear bond strength of conventional adhesive systems with and without collagen removal using 10 % sodium hypochlorite and self-etch adhesives. 48 human's molars were extracted for surgery and orthodontic reasons and after cleaning, they were stored in freezers (-18º C). The teeth were sectioned in an axial plan (mesio-distal), separated in two halves, vestibular and lingual. The teeth were mounted in self-cure resin and the labial and lingual surfaces were ground with sequential abrasive sandpaper to standardize the smear layer and expose the dentin with 2 mm of the thickness. The adhesion surface was delimited in 3 mm of diameter, the specimens were separated into six groups in accordance with adhesive system and dentin treatment: OBF - self-etch adhesive One-Up Bond F (Tokuyama); CSEB- self-etch primer Clearfil SE Bond (Kuraray); SB - Single Bond (3M); SBMP - Scotchbond Multi Uso Plus (3M); SBH - after acid etching was used at 10% sodium hypochlorite (AD Gel - Kuraray) during one minute and then Single Bond was used; SBMPH - after the acid etching sodium hypochlorite at 10% was used (AD GelKuraray) during one minute and then Scotchbond Multi Uso Plus was used. The composite resin Z-100 (3M) was inserted by incremental technique with a metallic matrix on a prepared surface. The shear test was realized in an lnstron Universal machine at 0,5 mm/min speed. The fractured surfaces were classified in stereomicroscopic (Karl Zeiss). The data obtained was analyzed by ANOVA and Tukey tests. The data showed the following values (in MPa): CSEB- 24,362; SB- 20,956; SBH - 17,825; OBF - 17,355; SBMP - 17,218; SBMPH- 14,169. We concluded that self-etch adhesive CSEB showed bond strength significantly higher than OBF and SBMP adhesives; the self-etch adhesive with acidificate primer showed bond strength statistically higher than where...